Oral Contraceptive Use and Psychiatric Disorders in a Nationally Representative Sample of Women - Cheslack-Postava, Keely (Arch Womens Ment Health, 2014)
PURPOSE: Examine the association between oral contraceptive use (any current use, duration and type) and major depression disorder (MDD), generalized anxiety disorder (GAD), and panic disorder (PD) in a nationally representative sample of women in the United States. METHODS: Data were drawn from 1,105 women aged 20–39 in the National Health and Nutrition Examination Surveys from 1999 to 2004. The associations between self-reported use of oral contraceptives in the past year and DSM-IV diagnosed and sub-threshold MDD, GAD, and PD in the past year were assessed comparing oral contraceptive users to all non-users, former users and former long-term users. RESULTS: Women using oral contraceptives had a lower past-year prevalence of all disorders assessed, other than sub-threshold MDD. When adjusted for confounders, women using oral contraceptives in the past year had significantly lower odds of sub-threshold PD, compared to former users (OR=0.34, 95% C.I. 0.14–0.84). Effects estimates were strongest for monophasic (versus multiphasic) oral contraceptive users. CONCLUSIONS: Hormonal contraceptive use was associated with reduced risk of subthreshold PD. A potential mental health benefit of hormonal contraceptives has substantial public health implications; prospective longitudinal studies are needed to confirm whether hormonal contraceptive use improves mental health.